2015
DOI: 10.3389/fpsyg.2015.00883
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the uncanny valley: the influence of repeated interactions and a robot's attitude on its perception

Abstract: The uncanny valley theory proposed by Mori has been heavily investigated in the recent years by researchers from various fields. However, the videos and images used in these studies did not permit any human interaction with the uncanny objects. Therefore, in the field of human-robot interaction it is still unclear what, if any, impact an uncanny-looking robot will have in the context of an interaction. In this paper we describe an exploratory empirical study using a live interaction paradigm that involved repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 51 publications
3
50
1
1
Order By: Relevance
“…Although Blascovich's hypothesis has been supported by several empirical findings (e.g., Baylor, 2009;Guadagno et al, 2007;Roubroeks, Ham, & Midden, 2011), other research has raised doubts on its unlimited validity. For instance, a recent robotics experiment showed that robots with high degrees of human likeness were rated as less trustworthy than more mechanical-looking counterparts (Złotowski et al, 2015). Offering a possible interpretation, the authors locate their result within the famous "uncanny valley" framework (Mori, 1970), which suggests that increasing a technology's human likeness will only promote its likability up to a certain threshold before an 'eerie' ambiguity between machine and human may evoke strong unease among observers.…”
Section: The Role Of Agent Appearancementioning
confidence: 97%
“…Although Blascovich's hypothesis has been supported by several empirical findings (e.g., Baylor, 2009;Guadagno et al, 2007;Roubroeks, Ham, & Midden, 2011), other research has raised doubts on its unlimited validity. For instance, a recent robotics experiment showed that robots with high degrees of human likeness were rated as less trustworthy than more mechanical-looking counterparts (Złotowski et al, 2015). Offering a possible interpretation, the authors locate their result within the famous "uncanny valley" framework (Mori, 1970), which suggests that increasing a technology's human likeness will only promote its likability up to a certain threshold before an 'eerie' ambiguity between machine and human may evoke strong unease among observers.…”
Section: The Role Of Agent Appearancementioning
confidence: 97%
“…The differential patterns of associations further emphasize the need to use both measures in parallel in order to capture discomfort towards robots in a more comprehensive manner (MacDorman & Entezari, 2015;Zlotowski, Sumioka et al, 2015). Most importantly, by delineating different aspects of discomfort scientists may ultimately be able to predict which aspect(s) compromise(s) people's willingness to engage with or accept robots (Ho & MacDorman, 2010;Patel & MacDorman, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research on this uncanny valley effect lacks consistency regarding the prevalence and explanation of the effect (Cheetham, 2017;Lay, Brace, Pike, & Pollick, 2016;Wang & Rochat, 2017). However, it may be that the effect is related to a discrepancy between expectations raised by an anthropomorphic "entity" and its observed behavior (Złotowski et al, 2015). Therefore, in the current state of most available technologies, the uncanny valley effect can pose a severe threat to the ecological validity of a task, as participants who feel disturbed by the perceived un-realism of the experimental setup are less likely to behave naturally.…”
Section: Enhancing Verisimilitudementioning
confidence: 99%